MEASUREMENT OF WILLINGNESS TO PAY LEVEL OF ORGANIC RICE CONSUMERS IN BANDAR LAMPUNG CITY - Desfaryani, Rini; Humaidi, Edy; Anggraini, Nuni (Agriprimatech, 2023)
Consuming healthy food has become a trend in the community, but healthy products tend to have high prices, while information on consumers' willingness to pay or the maximum price that consumers can afford is not yet available. This study aims to analyze the value of consumers' willingness to pay for organic rice. Analysis of the data used is descriptive analysis, and Contingent Valuation Method (CVM). The study was carried out in Bandar Lampung for six months, namely April - September 2022 and the sampling method used non-probability sampling, namely accidental sampling. The number of respondents in this study was 30. The results showed that consumers were willing to pay at a price 6% greater than the average price. The average organic rice is 26,670. Keywords: Willingness to pay, organic rice, Contingent Valuation Method